Three new species of Cyclocephala (Coleoptera: Scarabaeidae: Dynastinae) from Amazonian Peru and a checklist of Cyclocephala species in Peru - Paz, Fernando; Ratcliffe, Brett C.; Figueroa, Luis (Zootaxa, 2022)
The following new species of Cyclocephala Dejean, 1821 (Coleoptera: Scarabaeidae: Dynastinae: Cyclocephalini) are described from Peru: C. mateoi Paz & Ratcliffe, C. ukuku Paz & Ratcliffe, and C. hylaea Ratcliffe & Paz. A description, diagnosis, geographic distribution, notes on natural history, and illustrations are provided for each new species. Six Cyclocephala species are reported for the first time from Peru: C. emarginata Endrödi, 1964, C. guianae Endrödi, 1969, C. kuntzeniana Höhne, 1923, C. malyi Dupuis, 2014, C. ovulum Bates, 1888, and C. sylviae Dechambre, 1995. An updated, annotated list of the 81 Peruvian species of Cyclocephala is provided.